A last interglacial speleothem record from the Sieben Hengste cave system (Switzerland): implications for alpine paleovegetation - Marc Luetscher (PANGAEA, 2021)
Oxygen (d18O) and carbon (d13C) isotope data of a Last Interglacial speleothem (c. 134-117 ka) from the Sieben Hengste cave, Switzerland. The data underline the ocean control on North Alpine climate and provides firm evidence that the sample preserves a regional temperature record. The climate optimum is dated at 128.1 ± 1.2 ka.